Conjugates of Cisplatin and Cyclooxygenase Inhibitors as Potent Antitumor Agents Overcoming Cisplatin Resistance. Issue 6 (6th May 2014) - Neumann, Wilma; Crews, Brenda C.; Marnett, Lawrence J.; Hey‐Hawkins, Evamarie
Abstract Cyclooxygenase‐2 (COX‐2) is an enzyme involved in tumorigenesis, and inhibitors of the enzyme are increasingly used as adjuvant modulators in anticancer therapies due to their synergistic effects with traditional chemotherapeutics. COX‐2 is also reported to cause resistance towards antitumor agents, such as cisplatin. Here, the first covalently linked conjugates of cisplatin and COX inhibitors are reported. These conjugates exhibit concerted transport of both drugs into tumor cells and simultaneous action upon intracellular cleavage. These platinum(IV) complexes show highly increased cytotoxicity compared with cisplatin and are even able to overcome cisplatin‐related resistance of tumor cells. While the results reported show that COX‐2 inhibition is not directly responsible for the potent activities of these conjugates, they do represent useful tool compounds for the elucidation of the influence of COX inhibitors on the efficacy of antitumor agents.